Novel Sequence Variations in the Brain-Derived Neurotrophic Factor Gene and Association with Major Depression and Antidepressant Treatment Response - Licinio, Julio (Arch Gen Psychiatry, 2009)
CONTEXT: Variations in the brain-derived neurotrophic factor (BDNF) gene have been associated with psychiatric disorders, such as schizophrenia, bipolar and major depressive (MDD) disorder, and with antidepressant action. Deep sequencing of the BDNF gene may identify new genetic variations and bring further insights into psychiatric genetics. OBJECTIVE: To better characterize sequence variability in the BDNF gene. DESIGN: A genomic DNA region of 72 kb that contained the entire BDNF coding sequence and 5kb of flanking regions was re-sequenced in more than 500 subjects. SETTING AND PARTICIPANTS: Re-sequencing data was obtained in 264 controls and 272 MDD individuals collected from the Mexican-American community in Los Angeles; individuals were accessed by the same bilingual clinical research team. MAIN OUTCOME MEASURES: Identification of novel genetic polymorphisms in the BDNF gene, assessment of their frequencies and associations with MDD risk or response to antidepressants. RESULTS: We identified 83 novel single nucleotide polymorphisms (SNP): 30 in untranslated regions, in coding sequences, 37 in introns, and 12 in upstream regions. 3 of 4 rare novel coding SNPs were non-synonymous. Association analyses of MDD and controls revealed that 6 SNPs were associated with MDD (rs12273539, rs11030103, rs6265, rs28722151, rs41282918, rs11030101) and two haplotypes in different blocks were significantly associated with MDD. One recently reported 5′ UTR (untranslated region) SNP, rs61888800, was associated with antidepressant response after adjusting for age, gender, medication and baseline HAM-D21 score. CONCLUSIONS: We identified 83 new BDNF polymorphisms and found that genetic frequency variations across populations exist for this gene. One single SNP (rs12273539) and two haplotypes (one including Val66, another near exon VIIIh) remained significant after adjusting for multiple testing. One 5′ UTR SNP was associated with antidepressant response. Further studies using larger independent samples are needed to confirm this association and to understand the implications of these novel BDNF variations in psychiatric disorders.